2006
DOI: 10.1007/s10582-006-1058-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dibutyl phosphoric acid on zirconium extraction with diluted tributyl phosphate and the role of uranyl nitrate

Abstract: Distribution coefficients of zirconium (D Zr ) in the 30% TBP -aqueous HNO 3 solution extraction system rise 1000-2000 times with the increase of the dibutyl phosphoric acid (HDBP) concentration from 0 to 0.01-0.08 mol/L. A solvate with the molar ratio Zr: HDBP = 1 was found by IR spectroscopy and analytic methods in the initial range of HDBP concentration. In the presence of U(VI) D Zr decreases with the growing U concentration, however, the ratio of Zr distribution coefficient in the presence of HDBP (D AZr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In this study, the complexation of U and Pu with complexants found in the most common reprocessing process (i.e., plutonium uranium refining by extraction (PUREX)) was studied. ,, In this process, tributyl phosphate (TBP) in an immiscible organic solvent such as kerosene extracts Pu IV and U VI from aqueous solutions derived of dissolved SNF. The TBP can be degraded by both radiolysis and acid hydrolysis, resulting in a production of dibutyl phosphate (DBP) and monobutyl phosphate (MBP). , The primary degradation product, DBP, has adverse effects on the efficiency of U and Pu extraction including poor phase separation, , decreased mass-transfer coefficients, and poor fission-product/actinide separation factors. , In addition, many studies have reported that the complexation of DBP to Zr IV , Pu VI , and other metals results in the formation of a third layer made up of emulsions between the aqueous and organic interface. ,, This third phase and/or precipitate, which is formed, creates a large uncertainty in the given Pu and U concentration at a given stage of the PUREX process. Development of a method to quantitatively characterize actinide speciation in SNF will help elucidate the species leading to the formation of this third phase while helping maintain proliferation resistance and enhanced safety during reprocessing.…”
mentioning
confidence: 99%
“…In this study, the complexation of U and Pu with complexants found in the most common reprocessing process (i.e., plutonium uranium refining by extraction (PUREX)) was studied. ,, In this process, tributyl phosphate (TBP) in an immiscible organic solvent such as kerosene extracts Pu IV and U VI from aqueous solutions derived of dissolved SNF. The TBP can be degraded by both radiolysis and acid hydrolysis, resulting in a production of dibutyl phosphate (DBP) and monobutyl phosphate (MBP). , The primary degradation product, DBP, has adverse effects on the efficiency of U and Pu extraction including poor phase separation, , decreased mass-transfer coefficients, and poor fission-product/actinide separation factors. , In addition, many studies have reported that the complexation of DBP to Zr IV , Pu VI , and other metals results in the formation of a third layer made up of emulsions between the aqueous and organic interface. ,, This third phase and/or precipitate, which is formed, creates a large uncertainty in the given Pu and U concentration at a given stage of the PUREX process. Development of a method to quantitatively characterize actinide speciation in SNF will help elucidate the species leading to the formation of this third phase while helping maintain proliferation resistance and enhanced safety during reprocessing.…”
mentioning
confidence: 99%